2016
DOI: 10.1155/2016/4183432
|View full text |Cite
|
Sign up to set email alerts
|

Color-Matching and Blending-Effect of Universal Shade Bulk-Fill-Resin-Composite in Resin-Composite-Models and Natural Teeth

Abstract: Objectives. To assess visually color-matching and blending-effect (BE) of a universal shade bulk-fill-resin-composite placed in resin-composite-models with different shades and cavity sizes and in natural teeth (extracted and patients' teeth). Materials and Methods. Resin-composite-discs (10 mm × 1 mm) were prepared of universal shade composite and resin-composite of shades: A1, A2, A3, A3.5, and A4. Spectrophotometric-color-measurement was performed to calculate color-difference (ΔE) between the universal sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 11 publications
8
60
0
1
Order By: Relevance
“…These new universal composites have, according to the manufacturers, the concept of a universal translucency and opacity that could match the tooth color in different clinical situations. There are few reports about the color differences of these composites in posterior restorations, 11,33,34 but there were still no data evaluating these composites for anterior restorations. The Vita shade of a resin composite is determined by the color properties of hue and chroma, while the translucency is straight related to the lightness (value) of the material 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These new universal composites have, according to the manufacturers, the concept of a universal translucency and opacity that could match the tooth color in different clinical situations. There are few reports about the color differences of these composites in posterior restorations, 11,33,34 but there were still no data evaluating these composites for anterior restorations. The Vita shade of a resin composite is determined by the color properties of hue and chroma, while the translucency is straight related to the lightness (value) of the material 35 .…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous reports have shown that the blending effect was material and shade dependent and increased with the decrease in the restoration size and increase in translucency. 30 The acceptable threshold ranges from 2.0 to 4.0, and one-third of the studies in the literature have shown that 50% of observers accept a color difference at a threshold value of 3.7. 31 In one study, the CIELAB 50%:50% perceptual threshold in dentistry was ΔE*ab = 1.2, whereas the 50%:50% acceptance threshold was ΔE*ab = 2.7; more than half of the studies used a perceptual thresh- Though the EXs used the same spherical filler with an average particle size of 260 nm, E70 exhibited an acceptable match for the A4 artificial tooth at any cavity depth.…”
Section: Discussionmentioning
confidence: 99%
“…When two colors are displayed side by side, the blend, or perceived color of the area, shifts to the surrounding colors in the environment 29 . Previous reports have shown that the blending effect was material and shade dependent and increased with the decrease in the restoration size and increase in translucency 30 …”
Section: Discussionmentioning
confidence: 99%
“…This meant that OM blended in with the surrounding tooth structure, resulting in a reduced color difference between the two 6 . Abdelraouf et al 7 assessed the color match and BE of a universal shade composite (X‐TraFil) placed in composite resin models of different shades (Grandio; A1, A2, A3, A3.5, and A4) and cavity sizes, and in natural teeth. Spectrophotometric analysis was carried out to calculate the color difference ( ∆E ) between the universal shade and the other shades and visual scoring (VS) was done by seven observers.…”
Section: Introductionmentioning
confidence: 99%